1985
DOI: 10.1002/1097-4679(198509)41:5<651::aid-jclp2270410511>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Normative data on selected neuropsychological measures from a nonclinical sample

Abstract: Normative neuropsychological data are provided from a sample of 365, recruited from a nonclinical population. The sample was divided evenly between males and females, although males were somewhat overly represented in the youngest group, and females were somewhat overly represented in the oldest group. The measures included the Trail Making Test, Seashore Rhythm Test, Finger Tapping, Grooved Pegboard, and Dynamometer. The limited number of measures was a result of the time available to study each subject. Norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
116
2
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(131 citation statements)
references
References 12 publications
11
116
2
2
Order By: Relevance
“…As in previous studies, men tapped faster than women (Arnold et al, 2005;Ashendorf, Vanderslice-Barr, & McCaffrey, 2009;Bornstein, 1985;Christianson & Leathem, 2004;Coleman et al, 1997;Elias, Robbins, Walter, & Schultz, 1993;Gur et al, 2010;Heaton, Miller, Taylor, & Grant, 2004;Hubel et al, 2013aHubel et al, , 2013bMitrushina, Boone, Razani, & D'Elia, 2005;Peters, 1980;Peters & Campagnaro, 1996;Ruff & Parker;Schmidt et al, 2000;Ylikoski et al, 1998), outperforming women by three to five taps (Ashendorf et al, 2009;Mitrushina et al, 2005). Heaton and colleagues (2004) reported that about 16% to 20% of the test scores were accounted for by gender.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As in previous studies, men tapped faster than women (Arnold et al, 2005;Ashendorf, Vanderslice-Barr, & McCaffrey, 2009;Bornstein, 1985;Christianson & Leathem, 2004;Coleman et al, 1997;Elias, Robbins, Walter, & Schultz, 1993;Gur et al, 2010;Heaton, Miller, Taylor, & Grant, 2004;Hubel et al, 2013aHubel et al, , 2013bMitrushina, Boone, Razani, & D'Elia, 2005;Peters, 1980;Peters & Campagnaro, 1996;Ruff & Parker;Schmidt et al, 2000;Ylikoski et al, 1998), outperforming women by three to five taps (Ashendorf et al, 2009;Mitrushina et al, 2005). Heaton and colleagues (2004) reported that about 16% to 20% of the test scores were accounted for by gender.…”
Section: Discussionsupporting
confidence: 67%
“…Heaton and colleagues (2004) verified that education accounts for only about 2% to 4% of the variance in tapping scores. Still, as reported by other studies, best performances are often associated with more years of education, concerning not only higher levels of formal instruction (Ashendorf et al, 2009;Bornstein, 1985;Gur et al, 2010;Ruff & Parker, 1993), but also parental education (Gur et al, 2010).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In addition, the FAS test was inconsistently administered during the second assessment and could not be analyzed at that time because of small sample size. Normative data to assess severity of impairment were available for use on a few measures, including the following: Trailmaking (Bornstein, 1985; age, gender, and education adjustment), Stroop Test (Golden, 1978; age adjustment), Controlled Oral Word Fluency-FAS (Tombaugh et al, 1999; age and education adjustment), Selective Reminding (Larrabee et al, 1988; age and gender adjustment), and Wisconsin Card Sorting (Beatty, 1993;age adjustment).…”
Section: Methodsmentioning
confidence: 99%
“…Age, intelligence quotient (IQ), education, and gender may influence TMT performance (Davies 1968;Boll and Reitan 1973;Bornstein 1985;Wiederholt et al 1993;Gaudino et al 1995). However, the effects of gender on TMT performance are disputed (Heaton et al 1986;Waldmann et al 1992).…”
mentioning
confidence: 99%